Markers of early specialization and their relationships with burnout and dropout in swimming - Larson, H. K.; Young, B. W.; McHugh, T.-L. F.; Rodgers, W. M. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Empirical evidence directly associating early sport specialization with burnout and dropout is lacking, although a relationship is theorized. Research in this area relies on time-intensive retrospective interviews or questionnaires that generate large amounts of data. The optimal use of these data for assessing early specialization (ES) and its relationship with key criterion variablesis unclear. The purpose of this study was to add empirical evidence to the literature regarding ES, burnout, and dropout. This involved examining a large number of hypothesized markers of ES and reducing them to a smaller set useful for predicting burnoutand dropout. Survey data were collected from 137 swimmers, age 12-13 years, and their parents, including descriptions of swimmers` sport backgrounds from age 6 until present. Contrary to what was expected, the ES items were not positively related to burnout and dropout. The authors present several possible explanations, including key motivational considerations.